Comfort or conservation? Investigating patient choices between plastic and metal speculums - Torren A. Kalaskey; Kathryn G. Quillen; Kyle R. Knutsen; Kylie R. Bushko; Omar F. Dueñas-Garcia (PLoS ONE, 2026)
Background The pelvic examination is essential in gynecologic care but often causes discomfort and anxiety. Choice of plastic or metal speculums may influence patient comfort and adherence to screening, yet patient preferences and environmental considerations remain underexplored. Objective To assess patient preferences between plastic and metal speculums, identify factors influencing these preferences, and evaluate environmental concerns related to speculum use. Methods A cross-sectional survey was conducted among 203 patients receiving care at West Virginia University’s Obstetrics and Gynecology clinics between September 15, 2024 and June 16, 2025. Participants completed an anonymous online questionnaire assessing speculum preference, comfort factors, sanitation perceptions, and environmental awareness. Data were analyzed using descriptive statistics and chi-square tests. Results Plastic speculums were preferred by 49.8% of respondents, followed by no preference (32.5%) and metal speculums (17.7%). Younger participants (ages 18–35) showed a stronger preference for plastic. The speculum was identified as the most uncomfortable aspect of the exam by 34.4% of respondents, with temperature and positioning also frequently cited. Plastic was perceived as more sanitary by 45.8%. Environmental concern about plastic waste was higher among younger respondents and those preferring metal speculums. Despite ecological awareness, comfort during the exam was the predominant factor influencing preference. Conclusions Patient discomfort remains a primary barrier to maintaining consistent patient care in the field of obstetrics and gynecology, and this research found that the majority favor plastic speculums due to comfort despite environmental concerns in their lack of reusability. Efforts to improve pelvic exam experiences should address both comfort and sustainability, including innovations in speculum design, patient education on reusable options, and alternative screening methods. Further research is warranted to balance patient-centered care with environmental stewardship.